2010
DOI: 10.1523/jneurosci.0551-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Epileptogenesis Provoked by Prolonged Experimental Febrile Seizures: Mechanisms and Biomarkers

Abstract: Whether long febrile seizures (FSs) can cause epilepsy in the absence of genetic or acquired predisposing factors is unclear. Having established causality between long FSs and limbic epilepsy in an animal model, we studied here if the duration of the inciting FSs influenced the probability of developing subsequent epilepsy and the severity of the spontaneous seizures. We evaluated if interictal epileptifom activity and/or elevation of hippocampal T2 signal on magnetic resonance image (MRI) provided predictive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
290
2
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(312 citation statements)
references
References 82 publications
14
290
2
6
Order By: Relevance
“…Complex FSs were induced in rat pups on P9-P10 according to previous studies [11,15] with modifi cations. After weighing, the body temperature of the pups was raised in a chamber at 42-46°C.…”
Section: Generation Of Experimental Comple X Febrile Seizuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Complex FSs were induced in rat pups on P9-P10 according to previous studies [11,15] with modifi cations. After weighing, the body temperature of the pups was raised in a chamber at 42-46°C.…”
Section: Generation Of Experimental Comple X Febrile Seizuresmentioning
confidence: 99%
“…Most FSs are simple, having a brief duration and a low risk of developing epilepsy [9,10] . In contrast, one-third of FSs are 'complex', prolonged (>10-20 min) or repeated, and may be associated with a risk of subsequent mesial temporal sclerosis and intractable epilepsy [11][12][13] . Although some risk factors for developing epilepsy after FSs have been summarized in previous work [14] , these retrospective studies could not separate the effect of a FS itself (e.g., severity, seizure duration, and type) from that of pre-existing brain pathology (e.g., brain injury and non-FSs) and the infl uence of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a loss of distal dendritic inhibition in seizure rats may affect spatial coding by a direct entorhinal to CA1 distal-dendritic excitation (Brun et al, 2008;Leung, 2011). Abnormal place cell activity was found in animals with early-life seizures (Dube et al, 2009(Dube et al, , 2010. Attenuation in GABA B R function may be a critical component of epilepsy, and it may participate in a role of ''seizures beget seizures'' (Tsai et al, 2008).…”
Section: Significance and Implications Of Resultsmentioning
confidence: 99%
“…As a model of febrile seizures, hyperthermia-induced seizures in immature rats (Baram et al, 1997) were found to increase longterm seizure susceptibility and induce spontaneous seizures (Dube et al, 2010), without significant cell loss or sustained brain damage (Dube et al, 2000). Additionally, long-term behavioral changes have been reported after hyperthermic seizures (Chang et al, 2003;Dube et al, 2000Dube et al, , 2009Dube et al, , 2010. Long-term physiological changes after febrile seizure models include alteration of intrinsic membrane currents and an increased in GABA A receptor-mediated transmission in hippocampal slices in vitro (Chen et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…No evidence of hippocampal neuronal loss (using Nissl stain counting methods) have been found [24], but hyperexcitability in brain slices and an increase in seizure susceptibility have been reported [25]. More recently, spontaneous recurrent seizures have been recorded using concurrent hippocampal and cortical EEG video EEG monitoring [26,27].…”
Section: Injury To the Immature Brain To Induce Epileptogenesismentioning
confidence: 99%